Sosialisasi K3 : Pentingnya Pemahaman Titik Temu yang Aman Saat Bencana - Sari, Wedha; Ruhyat, Nanang (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Community service aims to increase understanding of safety and health (K3) related to fire, especially in establishing a safe meeting point when a disaster occurs. Through well-conducted outreach, participants are given knowledge about preventive measures, emergency measures, and the importance of having an organized evacuation plan in the face of fire. Interactive and participatory counseling methods are used to invite participants to be actively involved in learning, including emergency evacuation simulations. Before the socialization, participants filled out a questionnaire to measure their understanding and attitudes regarding fire K3. The results of the questionnaire are the basis for an initial evaluation to determine the level of knowledge and awareness of participants before socialization is carried out. After socialization, participants were also asked to fill out the same questionnaire to evaluate changes in their understanding, attitude and readiness towards fire. The evaluation results showed a significant increase in participants' understanding of preventive measures and emergency actions when a fire occurs. In addition, participants also showed an increase in their mental and physical readiness in dealing with emergency situations. This evaluation provides an indication that K3 socialization has had a positive impact on participants in increasing their awareness and preparedness for fires. As a further step, it is necessary to carry out regular monitoring and evaluation to ensure the continuity of the understanding and attitudes that have been improved by participants. Collaboration with related parties such as the fire department and related agencies can also strengthen efforts to improve community safety against fire disasters in residential areas.